Direct Susceptibility Testing of Positive Blood Cultures by Using Sensititre Broth Microdilution Plates - Chapin, Kimberle C. (American Society for Microbiology, 2003)
Traditional susceptibility testing of blood cultures requires overnight incubation in order to obtain isolated colonies. Susceptibility results can be reported up to 24 h sooner by using a bacterial pellet from the blood culture broth. This study evaluated the accuracy of direct susceptibility testing from positive ESP blood culture broths by using Sensititre broth microdilution plates compared to testing with isolated colonies. Practical inclusion criteria were applied to gram-positive organisms to avoid reporting susceptibilities for probable contaminants. All gram-negative organisms were tested directly. An aliquot of the blood culture was centrifuged, and the resulting pellet was used to make a 0.5 McFarland suspension. Microdilution plates were inoculated and interpreted according to the manufacturer's instructions. Colony counts were performed to ensure proper colony density was achieved. A total of 199 patient and seeded blood cultures were evaluated for both essential (within ±1 twofold dilution) and categorical (sensitive, intermediate, or resistant) agreement. Testing of 93 gram-positive isolates (1,214 antimicrobial agent-organism combinations) yielded 98% essential agreement and categorical error rates of 0.3% minor, no major (false resistance), and 1.7% very major (false susceptibility) errors. For 106 gram-negative isolates (1,828 antimicrobial agent-organism combinations), the essential agreement was 99%. Categorical error rates were 0.5, 0, and 2.0% for minor, major, and very major errors, respectively. Performance was comparable for both gram-positive and gram-negative isolates, as well as for both aerobic and anaerobic media. Using this direct testing methodology, reliable susceptibility results can be reported to physicians 24 h sooner, allowing earlier appropriate modification of antimicrobial therapy.